Profitable cannibalization - Norbert Schulz (University of Würzburg, Department of Economics, 2001)
Using a model with switching costs it is shown that firms may have an incentive to set up a new firm supplying to the same market under quite general conditions. The new firm attracts some market share of the founding firm. The start up firm is thus an act of cannibalization. Moreover, entry of the new firm may increase average prices. This is due to the fact that the new firm has more difficulties to overcome switching costs than incumbent firms. Competition may therefore be less intense.
Keywords: D43; L13; L41; 330; oligopoly; switching costs; price-increasing entry